2019
DOI: 10.1128/jvi.01740-18
|View full text |Cite|
|
Sign up to set email alerts
|

Risk Assessment of Fifth-Wave H7N9 Influenza A Viruses in Mammalian Models

Abstract: The fifth wave of the H7N9 influenza epidemic in China was distinguished by a sudden increase in human infections, an extended geographic distribution, and the emergence of highly pathogenic avian influenza (HPAI) viruses. Genetically, some H7N9 viruses from the fifth wave have acquired novel amino acid changes at positions involved in mammalian adaptation, antigenicity, and hemagglutinin cleavability. Here, several human low-pathogenic avian influenza (LPAI) and HPAI H7N9 virus isolates from the fifth epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…Qi et al (2018) also reported that the H7N9 HPAIVs displayed high pathogenicity in chickens, with the human viral strains also lethal to mice. Sun et al (2018) found that the H7N9 HPAIVs exhibited enhanced lethality in mice and caused more severe infections in ferrets compared to an H7N9 LPAIV.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Qi et al (2018) also reported that the H7N9 HPAIVs displayed high pathogenicity in chickens, with the human viral strains also lethal to mice. Sun et al (2018) found that the H7N9 HPAIVs exhibited enhanced lethality in mice and caused more severe infections in ferrets compared to an H7N9 LPAIV.…”
Section: Pathogenesismentioning
confidence: 99%
“…Guinea pigs and ferrets are two well-established animal models for the evaluation of transmissibility of influenza viruses (Gao et al 2009;Steel et al 2009;Herfst et al 2012;Imai et al 2012;Zhang et al 2013b). The H7N9 viruses, especially the human isolates, transmitted efficiently among guinea pigs or ferrets via direct contact (Belser et al 2013;Zhu et al 2013;Gabbard et al 2014;Luk et al 2015;Sun et al 2018). Compared with natural H5N1 viruses, which have never acquired respiratory droplet transmissibility, many studies have reported that both H7N9 LPAIV and HPAIV can transmit via respiratory droplets in guinea pigs and ferrets, although the efficiency of virus transmis- All six low pathogenic viruses and five of the six highly pathogenic viruses bound well to both human-type and avian-type receptors, whereas one of the six highly pathogenic viruses bound only to avian-type receptors.…”
Section: Transmissionmentioning
confidence: 99%
“…We recently demonstrated that despite no airborne transmissibility increase compared to LPAI A(H7N9) viruses, select HPAI A(H7N9) human isolates possess heightened mammalian virulence with an extended tissue tropism in animal models and a lowered threshold pH for membrane fusion, a trait potentially associated with enhanced transmission in mammals (Sun et al, 2018). However, a comprehensive understanding of the biological properties associated with HPAI A(H7N9) virulence and mammalian transmission has yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Neuraminidase inhibitor (NAI) resistance (R292K substitution in NA) was detected in both NA inhibitor-treated patients (Hu et al, 2013;Yen et al, 2013) and a few nonhuman-derived HP-H7N9 strains (Quan et al, 2018). Varied virulence and transmissibility has been confirmed in animal models by using circulating H7N9 viruses from wave five (Bao et al, 2019;Sun et al, 2019). Therefore, H7N9 AIV is classified as "an unusually dangerous virus for humans" by the World Health Organization (WHO, 3 ).…”
Section: Introductionmentioning
confidence: 99%